Antibonding ground state of adatom molecules in bulk Dirac semimetals - Marques, Y. [UNESP]; Obispo, A. E. [UNESP]; Ricco, L. S. [UNESP]; De Souza, M. [UNESP]; Shelykh, I. A.; Seridonio, A. C. [UNESP] (American Physical Society (APS), 2017)
The ground state of the diatomic molecules in nature is inevitably bonding, and its first excited state is antibonding. We demonstrate theoretically that, for a pair of distant adatoms placed buried in three-dimensional-Dirac semimetals, this natural order of the states can be reversed and an antibonding ground state occurs at the lowest energy of the so-called bound states in the continuum. We propose an experimental protocol with the use of a scanning tunneling microscope tip to visualize the topographic map of the local density of states on the surface of the system to reveal the emerging physics.